Focal prostate brachytherapy with 103Pd seeds. Issue 3 (March 2016) - Butler, Wayne M.; Merrick, Gregory S.
Highlights: First paper to address physics and radiobiology of focal brachytherapy using 103 Pd. Hemi-prostate and focal plans meet all target dosimetry and OAR constraints. Focal plans reduce the number of seeds and needles as expected. No evidence of superior biochemical control or morbidity reduction. Abstract: Purpose: Examine modifications to seed placement and target margins necessary to accomplish focal brachytherapy with 103 Pd. Methods: Our proposed focal brachytherapy program will be primarily favorable intermediate-risk patients with a unilateral index lesion confirmed by transperineal template-guided mapping biopsies (TTMB). The dimensions and location of the TTMB core with the index lesion were placed within the 3-D ultrasound planning volume. Implants were planned for the prostate and the focal targets with generous margins. Planning goals were to cover the target with the 125 Gy prescription dose and keep D90 (minimum dose covering 90% of the target) between 125% and 150% of the prescription while minimizing urethral and rectal hot spots. Radiobiological parameters — biologically effective dose (BED) and tumor control probability — were integrated over fractional sub-volumes and focal plans compared to whole gland brachytherapy. Results: A typical 30.1 cm 3 prostate was expanded to create a 50.6 cm 3 planning target volume (PTV) and needed 22 needles containing 86 103 Pd seeds of strength 3.20 U to deliver the prescribed dose. The hemi-prostate required 39 seeds in 12 needles, and the focal core expanded to a target volume of 11.6 cm 3 required 29 seeds in 8 needles. All cancerous PTVs and sub volumes had a tumoricidal BED while organs at risk (OAR) met the dose constraints minimizing morbidity. Conclusions: For this single case study, both hemi-prostate and focal brachytherapy using 103 Pd seeds met the same target dosimetric goals and OAR constraints as whole prostate plans but with the expected reduction in number of seeds and needles.